2022
DOI: 10.2147/mder.s339669
|View full text |Cite
|
Sign up to set email alerts
|

Novel Measure of Acetabular Cup Inclination and Anteversion During Total Hip Arthroplasty

Abstract: Purpose The purposes of the present research were to assess the accuracy and usability of the inertial navigation system (INS). Materials and Methods The accuracy of the device navigation subsystem was assessed using benchtop testing. The usability was assessed through simulated use with surgeons. These results were compared to recent cadaveric results for the same system. Results The navigation subsystem had an overall mean absolute error of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…A cadaveric study by Shatrov et al found a difference of 2.3° for acetabular version when comparing the devices measurements to postoperative CT-scans [ 61 ]. Accuracy for cup positioning with the device seems to be good and the registration method using the table tilt has been validated [ 60 , 61 ]. However, the literature on this technique is very limited and it needs to be validated in larger cohorts of living patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cadaveric study by Shatrov et al found a difference of 2.3° for acetabular version when comparing the devices measurements to postoperative CT-scans [ 61 ]. Accuracy for cup positioning with the device seems to be good and the registration method using the table tilt has been validated [ 60 , 61 ]. However, the literature on this technique is very limited and it needs to be validated in larger cohorts of living patients.…”
Section: Discussionmentioning
confidence: 99%
“…The operating table then needs to be tilted in a certain sequence; thereby, the system defines the reference axes that serve as a coordinate system. The literature on this device is limited to a few cadaveric studies [ 60 , 61 ].…”
Section: Cup Positioning Techniquesmentioning
confidence: 99%
“…As of the 27th of May 2021, the principal investigator consistently used an inertial imageless navigation device (Navbit Ò ) (NAV cohort). The same technique of registration was used as previously described by Walter et al [14] with one exception as the device was being used on the ipsilateral side instead of the contralateral side (Figure 2).…”
Section: Surgery and Navigationmentioning
confidence: 99%
“…To date, there has been a low use of navigation in THA procedures [12]. Inertial imageless navigation devices were introduced to avoid some of these problems as they are easy to use, had no radiation exposure, and were sterile in use [13,14]. This way, a patient can be located in a 3-dimensional space by just tilting the operating table (table tilt method), resulting in a functional baseline to the operating table (coronal plane).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation